The Colonial and Geographic Origins of Comparative Development - Raphael Auer (Swiss National Bank, Study Center Gerzensee, 2009)
While the direct impact of geographic endowments on prosperity is present in all countries, in former colonies, geography has also affected colonization policies and, therefore, institutional outcomes. Using non-colonized countries as a control group, I develop an empirical strategy that disentangles the partial effects of institutions and of endowments on income. I find that institutions are the main determinant of development, but that endowments have a sizeable direct impact, as well. Last, I apply the empirical strategy to examine the theories put forward by La Porta et al. (1999) and by Acemoglu et al. (2001), finding support for both theories, but also evidence that the authors' estimates are biased since they mix up the effect of the historical determinants of institutions with the sizeable direct impact of access to trade and of disease environment.
Keywords: O11; P16; P51; R11; N50; F54; 330; Growth; Institutions; Geography; Comparative Development; Colonialism; Entwicklung; Rohstoffvorkommen; Institutionelle Infrastruktur; Kolonialismus; Weltwirtschaftsordnung; Süd-Nord-Gefälle; Welt